Efforts To Increase Learning Motivation Using Problem Based Learning Models In Integrated Ips Lessons - Rianti Asmoro (Universitas Negeri Makassar, 2022)
The low learning motivation of students in learning Social Sciences requires teachers to continue to maximize the application of learning models and methods. This study aims to increase the motivation and learning outcomes of students of State Junior High School 34 Tebo Regency class VIII A by applying the Problem Based Learning learning model in the Odd semester of the 2021/2022 academic year. The research design used is a classroom action research design. Collecting data using learning outcomes tests and observations. From the data collected and obtained the average score of learning outcomes of Social Science lessons in cycle 1 is 71,28 and the average result in cycle II is 76,12. The results showed that by using the Problem Based Learning learning model, the learning motivation and learning outcomes of students increased